Sustainable development in period of COVID-19 pandemic - Mikulčić, Hrvoje; Zhang, Zhien; Baleta, Jakov; Klemeš, Jiří Jaromír (Journal of cleaner production, 2021)
COVID-19 pandemic has shown that sustainable development of energy, water and environment systems is essential for the basic life needs of humankind. Logistics problems, shortage of resources and goods, a crisis of traditional energy systems, all these COVID-19 caused problems show that available resources should be used with caution. This paper is an introduction article to the Virtual Special Issue that discusses some of the latest developments in three research topic areas, namely Energy, Water and Environment. These research topics emerged from the four Sustainable Development of Energy, Water and Environment Systems Conferences held in 2020. The purpose of the introduction article is to provide a brief introduction to the field and the articles included in this Journal of Cleaner Production Virtual Special Issue.
Keywords: Energy systems; Water and wastewater; Sustainable development; SDEWES; Environmental assessment; COVID-19